FAKTOR YANG MEMPENGARUHI PERILAKU SEKSUAL BERISIKO ANAK JALANAN DI KABUPATEN JEMBER PROPINSI JAWA TIMUR - Mury Ririanty (Fakultas Kesehatan Masyarakat, Universitas Jember, 2011)
Street children are vulnarable to the risk of sexuality transmitted diseaase as well as HIV and AIDS infections. This study aims to analyze personal and social factors influencing street children’s sexual behavior and its risk to Sexually Transmitted Disease and HIV-AIDS. The study is kuantitative research with cross sectional approach, involved a total of 62 samples derived from 178 Children On the Street population, aged 5-21 years old. Data were collected using questionnaires and were analysed using logistic regression statistical method. Social learning theory was applied as a base of the conceptual framework of the study so personal and environment factor are independent variable within dependent variable. The findings showed that the sexual behavior in children on the street is risk (51,6%), which was partly related to characteristics of sample are age, activity in the street, long time of children in the street, usage of addiktive substance, type of children on the street and attitude of heath reproductive, PMS and HIV/AIDS. The findings also showed that attitude of health reproductive, PMS and HIV/AIDS and support of leader group in count of probability 65,8%. The study suggested that construction children on the street to the fore it expected require to improve ugly knowledge and the attitude which are positive about health reproductive, PMS And HIV/AIDS, and approach to leader groups of children in the street. Others improvement advokasi reach and to children on the street regency also require to be improved. Keywords : Street Children, Sexual behavior, STDs, HIV-AIDS, Jember